Effects of a Mediterranean diet and structured exercise intervention on selected anthropometric, cardiovascular, and metabolic variables in physically inactive adults: a randomized controlled trial - Prieto-González, Pablo; Yagin, Fatma Hilal; Alghannam, Abdullah F.; Canli, Umut (Frontiers in Nutrition, 2025)
ObjectiveThe study aims to determine whether the combined implementation of Mediterranean diet (MD) adherence and structured physical exercise contributes to improvements in body composition and cardiometabolic health indicators in a physically inactive but otherwise healthy adult population.MethodsA randomized controlled trial (RCTs) was conducted with 125 physically inactive adults (61 males, 64 females) aged 35–50 years, free from cardiovascular, metabolic, or musculoskeletal conditions. Participants were assigned to either an 8-week intervention group (n = 62: 30 males, 32 females) combining Mediterranean diet adherence and supervised combined training (three endurance and two resistance sessions per week) or a control group (n = 63: 31 males, 32 females) instructed to maintain habits. Anthropometric, cardiovascular, and metabolic variables were assessed pre- and post-intervention under standardized conditions. A 2 × 2 × 2 mixed-design ANOVA (group × sex × time) was conducted, with Tukey's post hoc tests applied when significant differences were found.ResultsSignificant differences over time, between sexes, and between groups were observed in anthropometric, cardiovascular, and metabolic variables. In the experimental group (EG), both men and women experienced significant reductions in body mass (BM), BMI, fat percentage, waist circumference, waist-to-hip ratio (WHR), systolic and diastolic blood pressure, heart rate, double product, glucose, and low-density lipoprotein (LDL) cholesterol from pre- to post-test (all p < 0.05, with effect sizes ranging from small to large). Lean mass increased significantly only in the EG, while high-density lipoprotein (HDL) levels improved predominantly in women. Men and women differed significantly in body mass, BMI, fat percentage, lean mass, waist circumference, waist-to-hip ratio, heart rate, double product, glucose, HDL, and triglycerides at both time points (all p < 0.001). The EG showed significantly greater improvements compared to the control group after the intervention (p < 0.001 for most variables), confirming the intervention's effectiveness.ConclusionThis study provides robust evidence that a lifestyle intervention combining Mediterranean diet adherence with structured physical exercise is an effective and feasible strategy to enhance cardiometabolic health in physically inactive adults. Its multicomponent nature and consistent benefits across sexes support its integration into preventive health programs. Further research is warranted to assess the sustainability of these outcomes and their generalizability to broader populations.